Generational Differences in Learning-Oriented Work Commitment: The Mediating Role of Educational Context in Vocational and Professional Education in Bandung, Indonesia - Aisah, Aisah; Ahman, Eeng; Suryadi, Edi; Siti Hadijah, Hady; Yusriani, Sri (IJORER : International Journal of Recent Educational Research, 2026)
Objective: In the context of rapid transformation in vocational and professional education, this study aims to examine the influence of Generational Cohort on Learning-Oriented Work Commitment, with Educational Context serving as a mediating variable. Although generational differences are often assumed to shape learning behavior, empirical evidence explaining the mechanism through which these differences affect learning commitment remains limited. Method: This study employed a quantitative research design using a survey method. The sample consisted of learners enrolled in vocational and professional education programs in Bandung, Indonesia. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. Results: The findings indicate that Generational Cohort has a significant effect on Educational Context, while Educational Context significantly influences affective, continuance, and normative learning commitment. Moreover, Educational Context fully mediates the relationship between Generational Cohort and all dimensions of learning-oriented work commitment, indicating that generational differences do not directly determine learning commitment but operate through contextual learning conditions. Novelty: This study offers a critical theoretical contribution by challenging the dominant assumption that generational differences directly determine learning commitment. By empirically demonstrating the full mediating role of Educational Context, this research reframes generational differences as contextual rather than deterministic factors. The findings advance educational theory by positioning Educational Context as the central mechanism through which generational characteristics are translated into learning-oriented work commitment in vocational and professional education.